Вычислите, , пример 4. (на знание степеней)

Валериевич Валериевич    1   03.09.2019 09:14    1

Ответы
Варёна Варёна  06.10.2020 14:31

А) 0

Пошаговое объяснение:

\dfrac{a^{\frac{1}{3}}(a - 8b)}{a^{\frac{2}{3}}+2a^{\frac{1}{3}}b^{\frac{1}{3}}+4b^{\frac{2}{3}}} :(1-2a^{-\frac{1}{3}}b^{\frac{1}{3}})-a^{\frac{2}{3}}=\\\\=\dfrac{a^{\frac{1}{3}}(a^{\frac{1}{3} } - 2b^{\frac{1}{3} })(a^{\frac{2}{3}}+2a^{\frac{1}{3}}b^{\frac{1}{3}}+4b^{\frac{2}{3}})}{a^{\frac{2}{3}}+2a^{\frac{1}{3}}b^{\frac{1}{3}}+4b^{\frac{2}{3}}} :(1-2a^{-\frac{1}{3}}b^{\frac{1}{3}})-a^{\frac{2}{3}}==(a^{\frac{1}{3}}(a^{\frac{1}{3} } - 2b^{\frac{1}{3} })):\dfrac{a^{\frac{1}{3} } - 2b^{\frac{1}{3} }}{a^{\frac{1}{3} }} -a^{\frac{2}{3} }=a^{\frac{2}{3} }-a^{\frac{2}{3} }=0

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика